Pengaruh Hybrid Learning Berbasis Tutor Sebaya terhadap Hasil Praktik Pengelasan pada Siswa SMK : The Effect of Peer Tutor-Based Hybrid Learning on Welding Practice Outcomes in Vocational High School Students - Denhas Wicaksono; Dwi Agus Sudjimat; Yayi Febdia Pradani (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to examine the effect of a peer-tutor-based Hybrid Learning model on SMAW welding performance in the 3G position among 11th-grade Welding Engineering students at SMKN 10 Malang. This study involved 2 groups of students: those who studied using peer-tutor-based hybrid learning and those who studied without peer-tutor assistance. The research method used was a quasi-experimental posttest-only control-group design. The research subjects comprised two classes: a control and an experimental class, each with 30 students. The research instrument was an SMAW welding practice test in the 3G position, assessed using a welding results assessment rubric. Data were analyzed using descriptive statistics, the Kolmogorov–Smirnov normality test, Levene's homogeneity test, and an independent-samples t-test. The results showed a significant difference in students' welding practice between the control and experimental classes, with a significance value of sig. <0.05. Thus, it can be concluded that the peer-tutor-based hybrid learning model has a significant effect on SMAW welding performance in the 3G position for vocational high school students. The application of a peer-tutor-based hybrid learning model has a significant effect on SMAW welding performance in the 3G position for students at SMKN 10 Malang, compared to the control class without peer-tutor assistance.